Natural and Cultural Processes Influencing Gene Flow Among Wild (atoq papa), Weedy (araq papa and k’ipa papa), and Crop Potatoes in the Andean Region of Southern Peru - Parra-Rondinel, Fabiola; Casas, Alejandro; Begazo, Domingo; Paco, Amalia; Márquez, Eusebia; Cruz, Aldo; Segovia, Jorge; Torres-García, Ignacio; Zarazúa, Mariana; Lizárraga, Luis; Torres-Guevara, Juan (Frontiers in Ecology and Evolution, 2021)
The Andean region is one of the areas with the earliest signs of food production systems and highest agrobiodiversity of the world, resulted from millennia of domestication. Nearly 3000 varieties of cultivated potatoes currently occurring in Peru. Such diversity has sources of variation in wild (atoq papa) and weedy (araq papa and k’ipa papa) potatoes that coexist with crops, but their variation, interactions and mechanisms influencing diversification processes require studies. To have a panorama of the variation and mechanisms influencing it in a regional setting, we studied biocultural factors favouring potatoes diversity in communities of Cusco and Apurimac, Peru. Our study documented the regional variation of wild, weedy, and cultivated potatoes recognized by Quechua people and conducted semi-structured interviews to document their use, cultural value, and gene flow management. We also studied their phenology, floral biology, flower visitors, and conducted experimental crosses between wild S. candolleanum and 30 varieties of crops. We identified the wild potatoes S. acaule, S. brevicaule and S. candolleanum and 53 varieties of araq papa. The latter provide nearly one third of the annual consumption of tubers by people interviewed and are valued, maintained and managed in crop fields. People recognized that crosses between wild, weedy, and cultivated potatoes occur, and identified flower visitors and frugivorous. Overlap of blooming periods and flower visitors of wild, weedy, and cultivated potatoes was recorded. Flower visitors are shared among the different potato species and varieties, being particularly relevant bumble bees in pollination of all taxa studied. We recorded seed production in nearly 35% of the experimental crosses. K’ipa papas are sets of mixtures of plants resulting from remaining tubers of cultivated potatoes, but also those from seeds that may result from hybridization of wild, weedy, and cultivated potatoes. Since local people commonly use k’ipa papa and some of them are kept for planting in chacras, sexual reproduction in k’ipa papas is possibly one main mechanism of variation and source of new varieties of crops. Maintaining wild and weedy potatoes, and the natural and cultural mechanisms of gene flow is crucial for in situ conservation and generation of potato variation.